Isidore of Seville and his reception in the early Middle Ages : transmitting and transforming knowledge - Fear, A. T.; Fouracre, Paul; Wood, Jamie (Late antique and early medieval Iberia, 2016)
Isidore of Seville (560-636) was a crucial figure in the preservation and sharing of classical and early Christian knowledge. His compilations of the works of earlier authorities formed an essential part of monastic education for centuries. Due to the vast amount of information he gathered and its wide dissemination in the Middle Ages, Pope John Paul II even named Isidore the patron saint of the Internet in 1997. This volume represents a cross section of the various approaches scholars have taken toward Isidore's writings. The essays explore his sources, how he selected and arranged them for posterity, and how his legacy was reflected in later generations work across the early medieval West. Rich in archival detail, this collection provides a wealth of interdisciplinary expertise on one of history's greatest intellectuals.
Keywords: Isidore, : of Seville, Saint, : -636 : Congresses; Isidore, : of Seville, Saint, : -636 : Influence : Congresses; Isidorus Hispalensis; Bishops : Spain : Seville; Christian literature, Early : Latin authors : History and criticism; Fathers of the church; Influence (Literary, artistic, etc.)